2018
DOI: 10.3345/kjp.2018.61.8.231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of underweight and wasting in Iranian children aged below 5 years: a systematic review and meta-analysis

Abstract: Purpose Wasting and underweight are the 2 main indicators of children’s undernutrition. We aimed to estimate the prevalence of undernutrition at the national level in Iran.Methods We performed a search for original articles published in international and Iranian databases including MEDLINE, Web of Science, Google Scholar, Scopus, CINHAL (Cumulative Index to Nursing and Allied Health Literature), Scientific Information Database, Irandoc, Iranmedex, and Magiran during January 1989–August 2017. Seven keywords, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Studies have generally reported that sex-based differences may be due to various factors, such as differences in nutritional status, hormone levels, physiological and behavioral characters, and socioeconomic status. Cultural differences and sex-based differences can affect a child’s nutritional status, health, and care [34,38-42]. In the present study, the attitude of the Iranian people towards obesity and overweight in boys and girls and their degree of sensitivity to fitness can explain the higher prevalence of overweight and obesity in boys than in girls because obesity and overweight are less socially acceptable in girls than in boys [43].…”
Section: Discussionmentioning
confidence: 78%
“…Studies have generally reported that sex-based differences may be due to various factors, such as differences in nutritional status, hormone levels, physiological and behavioral characters, and socioeconomic status. Cultural differences and sex-based differences can affect a child’s nutritional status, health, and care [34,38-42]. In the present study, the attitude of the Iranian people towards obesity and overweight in boys and girls and their degree of sensitivity to fitness can explain the higher prevalence of overweight and obesity in boys than in girls because obesity and overweight are less socially acceptable in girls than in boys [43].…”
Section: Discussionmentioning
confidence: 78%
“…[ 12 - 14 ] Previous studies have found insufficient food intake as the main reason for this finding. [ 12 - 14 ] Moreover, behavioral problems related to eating and lack of proper education of parents are the next influential factors in this deficiency. [ 12 - 14 ] Lack of adequate protein intake impairs height weight growth throughout affecting musculoskeletal growth.…”
Section: Introductionmentioning
confidence: 99%
“…PEM is the most common type of malnutrition among Iranian children,[ 12 - 14 ] and usually the median protein intake among Iranian children is less than recommended for their age group. [ 12 - 14 ] Previous studies have found insufficient food intake as the main reason for this finding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations